Implementasi Pembelajaran Kitab Fathul Qorib pada pemahaman hukum Islam di Pesantren Darul Fiqhi Lamongan - Aprilianto, Dwi; Sagita Putri, Herfindah (Akademika, 2023)
This research is entitled Implementation of Learning the Book of Fathul Qorib in Improving Understanding of Islamic law Santri Pondok Pesantren Darul Fiqhi Deket Lamongan by using this qualitative. Learning is an activity that has the goal of teaching students. Learning the book of Fathul Qorib is essential for students to learn to improve understanding of uislamic law. This study aims to determine the understanding of islaic law Â when using the book Fathul Qorib. This study is motivated by the fact that the book Fathul Qorib is essential, especially with regard to worship. At the same time, the ubudiyah of Islamic law series includes thoharoh or purification, prayer, zakat, fasting, and pilgrimage. The implementation of studying the book of Fathul Qorib at the Darul fiqhi Islamic boarding school has fulfilled three stages of implementation, namely implementation, planning, and evaluation. Based on the results of observations made by researchers from the series of several Islamic law above, it shows that the students in terms of understanding has increased very broadly and deeply after studying the book of Fathul Qorib.